Spillover effects of FDI and trade on demand for skilled labour in Malaysian manufacturing industries - Mohamad Yunus, Norhanishah; Said, Rusmawati; W. Azman-Saini, W. N. (Universiti Sains Malaysia Press, 2015)
Malaysia has been among the top recipients of foreign direct investment (FDI) in the world. However, the benefit of FDI spillovers on skill upgrading in Malaysia remains ambiguous. This is particularly important to countries such as Malaysia, as the volume of FDI inflows has continued to increase over time. The present study adds to the literature investigating the effects of FDI as a spillover channel through which foreign trade enhances the relative demand for skilled labour in 50 Malaysian manufacturing industries during the 2000–2008 period. Our empirical results based on the generalised method-of-moments system estimator reveal that the spillover effects of FDI are significant for skill upgrading and, in turn, lead to increased demand for skilled labour. Although the coefficient for FDI indicates a negative relationship between FDI and skilled labour demand, the effect of FDI is positive and statistically significant. This result gives an indication that the spillover effects of FDI appear to be quickly assimilated by workers in the Malaysian manufacturing industries through the "learning effect" and that the fast pace is biased towards skilled workers. Nevertheless, this study finds no evidence of spillover effects from trade on the demand for skilled labour. The findings from this study potentially contribute to long-run FDI policy, especially to encourage FDI inflows into low receiving industries.